Wigner Distribution Functions and the Representation of Canonical Transformations in Time-Dependent Quantum Mechanics - Schuch, D.; Moshinsky, M. (Symmetry, Integrability and Geometry: Methods and Applications, 2008)
For classical canonical transformations, one can, using the Wigner transformation, pass from their representation in Hilbert space to a kernel in phase space. In this paper it will be discussed how the time-dependence of the uncertainties of the corresponding time-dependent quantum problems can be incorporated into this formalism.